Postcommunism and the body politic - Berry, Ellen E. (Genders, 1995)
The postcommunist moment in the so-called Second World--Central and Eastern Europe and the former Soviet Union--has dramatically exposed the opportunities and dangers that arise when the political, cultural, and economic foundations of a society are de- and then re-structured. Gender roles and relations, expressions of sexuality or attempts to recontain them, representations of the body, especially the female body, and the larger, cultural meanings it assumes, are particularly marked sites to witness the performance of complex national dramas of crisis and change. This groundbreaking volume tur.